Polycythemia with Renal Cell Carcinoma and Normal Erythropoietin Level - Jonathan Kopel; Pranav Sharma; Irfan Warriach; Sriman Swarup (Case Reports in Urology)
A 61-year-old obese Caucasian male with past medical history of smoking, hypertension, chronic obstructive pulmonary disease (COPD), and sleep apnea presented to the hematology clinic with polycythemia. Despite the newly-diagnosed polycythemia, the patient denied any significant symptoms or history of blood clots. Further evaluation with computerized tomography (CT) and ultrasound showed a large renal mass suspicious for renal cell carcinoma of the right kidney. An incidental abdominal aortic aneurysm (AAA) measuring was also appreciated on imaging. Subsequent histological sections of the tumor showed cell renal cell carcinoma. Though previously reported, the concomitant finding of an AAA with renal cell carcinoma with a normal erythropoietin levels is surprising. Given the surgical complications associated with concomitant conditions with renal cell carcinoma, further investigation into paraneoplastic syndromes secondary to renal cell carcinoma remains open to investigation.